The sum of Fibonacci sequence

Algebra Level 3

We know the Fibonacci sequence is { F n } = 0 , 1 , 1 , 2 , 3 , 5 , 8 , 13 , 21 , 34 , 55 \{F_n\} = 0, 1, 1, 2, 3, 5, 8, 13, 21, 34, 55 \cdots and that F n = F n 1 + F n 2 F_{n} = F_{n-1} + F_{n-2} .

What is F 1 + F 2 + F 3 + + F n F_{1} + F_{2} + F_{3} + \cdots + F_{n} ?

F n + 1 F_{n+1} F n + 2 1 F_{n+2}-1 F n + 2 F_{n+2} F n + 1 1 F_{n+1}-1

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Chew-Seong Cheong
Jan 24, 2021

Let S n = k = 0 n F k S_n = \displaystyle \sum_{k=0}^n F_k . Then we have S 0 = 0 = F 2 1 S_0 = 0 = F_2 - 1 , S 1 = 1 = F 3 1 S_1 = 1 = F_3 - 1 , S 2 = 2 = F 4 1 S_2 = 2 = F_4 - 1 , S 3 = 4 = F 5 1 S_3 = 4 = F_5 -1 , \cdots . It would appear that S n = F n + 2 1 S_n = F_{n+2}-1 . We can prove the claim is true for all n 0 n \ge 0 by induction . The claim is true for n = 0 n=0 . Assuming the claim is true for n n , then

S n + 1 = S n + F n + 1 = F n + 2 1 + F n + 1 = F n + 3 1 S_{n+1} = S_n + F_{n+1} = F_{n+2} - 1 + F_{n+1} = F_{n+3} - 1

The claim is also true for n + 1 n+1 , therefore k = 0 n F k = F n + 2 1 \displaystyle \sum_{k=0}^n F_k = \boxed{F_{n+2}-1} is true for all n 0 n \ge 0 .

Mathematical induction! What a great solution!

Raymond Fang - 4 months, 2 weeks ago

You can see my another problem: What is the sum of all the values of x?

Raymond Fang - 4 months, 2 weeks ago
Raymond Fang
Jan 24, 2021

Let S = F 1 + F 2 + F 3 + + F n . S=F_{1}+F_{2}+F_{3}+ \cdots +F_{n}. \newline So 2 S = ( F 1 + F 1 ) + ( F 2 + F 2 ) + ( F 3 + F n 2 ) + ( F n 1 + F n 1 ) + ( F n + F n ) = F 1 + ( F 1 + F 2 ) + ( F 2 + F 3 ) + ( F n 2 + F n 1 ) + ( F n 1 + F n ) + F n . \newline 2S \newline =(F_{1}+F_{1})+(F_{2}+F_{2})+(F_{3}+ \cdots F_{n-2}) + (F_{n-1} + F_{n-1}) + (F_{n} + F_{n}) \newline =F_{1}+(F_{1}+F_{2})+(F_{2}+F_{3})+ \cdots (F_{n-2} + F_{n-1}) + (F_{n-1} + F_{n}) + F_{n}. \newline And we also know: F n = F n 1 + F n 2 . F_{n} = F_{n-1} + F_{n-2}. \newline So 2 S = F 1 + F 3 + F 4 + + F n + 1 + F n = S F 2 + ( F n + 1 + F n ) 2 S = S 1 + F n + 2 S = F n + 2 1 \newline 2S \newline = F_{1} + F_{3} + F_{4} + \cdots + F_{n+1} + F_{n} \newline = S - F_{2} + (F_{n+1} + F_{n}) \newline 2S = S - 1 + F_{n+2} \newline \boxed{S = F_{n+2} - 1}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...